Cooperative effect of Cr and Al elements on passivation enhancement of eutectic high-entropy alloy AlCoCrFeNi2.1 with precipitates. (10th February 2023) - Duan, Xiaotian; Han, Tiezhuang; Guan, Xiao; Wang, Yuning; Su, Huhu; Ming, Kaisheng; Wang, Jing; Zheng, Shijian
Abstract: In conventional corrosion-resistant alloys, precipitation usually reduces corrosion resistance severely by weakening passive films locally. In this work, we found that the aging-treated AlCoCrFeNi2.1 samples, which have abundant nanosized L12 and body-centered cubic (BCC) precipitates in the lamellar face-centered cubic (FCC) and B2 phases, displayed better corrosion resistance than solution-treated AlCoCrFeNi2.1 samples without precipitates. In the AlCoCrFeNi2.1 alloy, the FCC phase with L12 precipitates and the B2 phase with BCC precipitates were protected by passive films enriched with Cr and Al elements, respectively. Moreover, the Al-rich passive film of the B2 phase was less stable than the Cr-rich passive film of the FCC phase, so B2 phase dissolved preferentially. The Cr-rich passive film of the FCC phase remained stable with the formation of Al-rich L12 precipitates inside the phase because those precipitates with the size of ∼5 nm were too small to affect the composition of the Cr-rich passive film. The formation of Cr-rich BCC precipitates within the B2 phase increased the content of the Al element inside the phase, improving the stability of Al-rich passive film on the B2 phase. Furthermore, BCC precipitates with the size of ∼30 nm were protected by Cr-rich passive film, which could inhibit the expansion of corrosion pits. Thus, the corrosion resistance of eutectic high-entropy alloy AlCoCrFeN2.1 was unprecedentedly enhanced by the precipitation of BCC precipitates. Our study could provide an attractive strategy for designing high-entropy alloys with excellent corrosion resistance and high strength.